THE STATE OF DEVELOPMENT OF ARTIFICIAL INTELLIGENCE IN THE DIGITAL ECONOMY - Abduganiyev Elbek Abdukhamedovich (Ecominds Press, 2025)
This article examines the history of artificial intelligence in the context of the digital economy, neural networks and machine learning - the basic concepts of artificial intelligence, the economic scale of artificial intelligence in the global economy and the areas of application of artificial intelligence.
Keywords: Digital economy, artificial intelligence, patent, global economy, Facebook, Google, Amazon, Apple, Microsoft, Baidu, McKinsey.